Deaf Sociality e Medical Intervention - Loce-Mandes, Fabrizio (Antropologia Pubblica; Vol 3 No 1 (2017): Richiedenti asilo e sapere antropologicoDO - 10.1473/anpub.v3i1.106, 2017)
Michele, Friedner. Valuing the Deaf World in Urban India , Pag. 196, New Brunswick – New Jersey – London, Rutgers University Press, 2015 Laura, Mauldin. Made to Hear. Cochlear Implants and Raising Deaf Children , Pag. 215, Minneapolis, University of Minnesota Press, 2016.